2022
DOI: 10.7241/ourd.2022e.19
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of propranolol in a fulminant ulcerated infantile hemangioma

Abstract: Infantile hemangiomas (IHs) are the most common tumors of infancy, with a global prevalence estimated at 1% to 10% of infants. Most hemangiomas are small and regress spontaneously without a need for intervention. However, 5% to 10 % of hemangiomas may cause serious complications and require treatment. Herein, we report the case of a two-month-old female infant with a left hemifacial hemangioma, which became severely ulcerated after the introduction of propranolol. We also report a good improvement afterwards d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recent cases in the literature have reported worsening ulceration of infantile hemangiomas after initiation or escalation of propranolol. 18,19 Our secondary analysis of accelerated propranolol initiation dosing in the setting of infantile hemangiomas with active ulcerations or at high risk of ulcerating demonstrated that accelerated initiation of propranolol at the 2 mg/kg/day dose did not demonstrate any increase in the incidence of new or worsening ulceration when compared to the 1 mg/kg/day dose. Additionally, while there was a longer treatment duration for the 1 mg/kg/day group compared to the 2 mg/kg/day group, this difference was not significant.…”
Section: Discussionmentioning
confidence: 90%
“…Recent cases in the literature have reported worsening ulceration of infantile hemangiomas after initiation or escalation of propranolol. 18,19 Our secondary analysis of accelerated propranolol initiation dosing in the setting of infantile hemangiomas with active ulcerations or at high risk of ulcerating demonstrated that accelerated initiation of propranolol at the 2 mg/kg/day dose did not demonstrate any increase in the incidence of new or worsening ulceration when compared to the 1 mg/kg/day dose. Additionally, while there was a longer treatment duration for the 1 mg/kg/day group compared to the 2 mg/kg/day group, this difference was not significant.…”
Section: Discussionmentioning
confidence: 90%